Molecular Docking of Active Compound of Lavandula angustifolia Mill Essential Oil against N-methyl-D-aspartate (NMDA) Receptor - Baiq Risky Wahyu Lisnasari; Aniek Setiya Budiatin; Chrismawan Ardianto; Junaidi Khotib (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2022)
Background: Lavender oil is widely known to possess a relaxant effect to relieve stress, anxiety, and depression. Linalyl acetate, linalool, geranyl acetate, and β-caryophyllene were the major constituents of lavender oil that potentially act on NMDAR (N-methyl-d-aspartate receptors), and emerging targets in the treatment of depression. Objective: This study aims to predict the binding of lavender compounds to NMDA receptors using an in silico model. Methods: The ligands of the docking study were four major chemical compounds of lavender oil, i.e., linalyl acetate, linalool, geranyl acetate, and β-caryophyllene. 5YE was defined as a native ligand, while memantine, an NMDAR antagonist, was used as a reference ligand. The NMDAR structure was taken from Protein Data Bank (ID 5H8Q), while the lavender compound was sketched in Chem3D. Autodock 4.2 was used to perform the docking analysis. Results: The result showed that beta-caryophyllene had the most potent interaction with NMDAR (free binding energy was -8.02 kcal/mol and inhibitory constant was 1.32 µM). Conclusion: The docking results suggest that beta-caryophyllene could be an NMDAR antagonist and be developed as a treatment for depression.